P312 Erythrocyte methotrexate polyglutamate concentrations in patients with Crohn's Disease: towards a new therapeutic drug monitoring tool. (27th May 2021) - Van de Meeberg, M; Lin, M; Seinen, M; Fidder, H; Oldenburg, B; Bouma, G; de Jonge, R; Bulatović Ćalasan, M
Abstract: Background: Methotrexate (MTX) is an immunomodulatory drug for patients with Crohn's Disease (CD), used as first-line therapy, as a second-line in case of failure to thiopurine, and concomitantly with anti-TNFα agents to decrease production of anti-drug antibodies. Nevertheless, MTX is underutilised in the treatment of CD, despite its proven efficacy and good safety profile. This is for a large part due to the lack of therapeutic drug monitoring (TDM) of MTX because no stable plasma MTX levels are reached. Intracellular MTX-polyglutamates (MTX-PGs), formed after folylpolyglutamate synthetase attaches glutamate residues to MTX, could be used as a TDM tool as MTX-PG is thought to mediate MTX's efficacy. We present the results of our cross-sectional study in CD patients, aiming to gain insight into erythrocyte MTX-PG levels. Methods: CD adults on MTX treatment who visited the outpatient clinic of Amsterdam UMC between May 2019 and February 2020 were included consecutively. An established LC-ESI-MS/MS method 1 was used to measure erythrocyte MTX-PGs. Results: Nineteen patients were included. Mean disease duration was 17 years (SD±13.7). Montreal disease location and behaviour were as follows (n=): L1 = 2, L2 = 4, L3 = 13; B1 = 11, B2 = 5, B3 = 3. Only 4 patients had a flare according to Physician Global Assessment. Twelve patients received MTX monotherapy, whereas 7 patients were on concomitant anti-TNFα agents. The mean dose of MTX was 15.5 mg (SD±2.8) and 12 (63%) patients had subcutaneous (sc.) MTX. We successfully measured MTX-PG2-5 in 18 patients, showing substantial variability in measured concentrations of total MTX-PG(tot) and the individual species. The median MTX-PGtot was 117.1 nmol/L [min:46.4-max:358.7] with preferential accumulation of MTX-PG3 (43.1 [15.3-96.1]); the least predominant species being MTX-PG5 (9.4 [1.1-24.1]). Patients on sc. compared to oral MTX had higher MTX-PGtot levels (177.8 [58.8-358.7] vs. 93.2 [46.4-120.8] nmol/L, p=0.067) and significantly higher long-chain MTX-PG4-5 levels (55 [3.7-84.3] vs. 8.9 [2.4-15.0] nmol/L, p=0.010); see figure. Conclusion: We showed that erythrocyte MTX-PGs can be measured in CD patients by tandem MS. Large variability in concentrations was demonstrated, similar to our previously published results in rheumatoid and juvenile arthritis 2, 3 which is a pre-requisite for MTX-PG use as a TDM tool. We showed for the first time that MTX-PG accumulation was higher in sc. MTX vs. oral MTX treatment. This work provides the first step towards establishing TDM for MTX in CD, a goal we aim to realize in our upcoming longitudinal study. References: Den Boer et al ., J Rheumatol 2014. Bulatović et al ., Ann Rheum Dis 2015. De Rotte et al., Ann Rheum Dis 2015.